Habitat restoration requires landscape‐scale planning. Issue 2 (April 2015) - Helm, Aveliina
Abstract Habitat restoration cannot be considered simply as an act of re‐creating the original environmental conditions and biota, neglecting the significance of the context of the surrounding landscape and overlooking the need to recreate metapopulation dynamics for target species. In this issue, Prach et al. show the importance of the availability of target species in the surrounding landscape to achieve successful restoration.